Multiple-criteria Decision Analysis (MCDA) of the Schemes to Terminate Small House Concessionary Right in Hong Kong - Wang, Chuyun; Zhao, Ziyun (International Journal of Social Sciences and Public Administration, 2024)
The entitlement of indigenous male residents in the New Territories to construct a small house is commonly known as small house concessionary right (ding rights). People from all walks of life, such as property developers, government officials, and indigenous inhabitants, have raised various proposals to cancel ding rights. In regard to the various proposals, policy objectives and the related criteria shall be evaluated to decide the feasibility of the initiatives. This study shows that the securitization of ding rights is the most desirable way to satisfy the interests of various groups.